Observation of the χb1(3P) and χb2(3P) and Measurement of their Masses; Physical Review Letters; Vol. 121, iss. 9 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2018, 2018)
Title screen